Farming the sun : the political economy of agrivoltaics in the European Union - Vezzoni, Ruben (Springer Nature, 2025)
What kind of agricultural practices do agrivoltaic systems incentivise? Under what circumstances can they deliver the promised benefits, and who is likely to bear the costs? Presented as a win–win solution for developing solar energy while enhancing farmland productivity, agrivoltaics offer several advantages—including decentralised electrification, improved crop yield, and thus increased farmers’ income. Compared to traditional utility-scale solar, however, agrivoltaics generally entail higher installation costs and material requirements, lower energy generation, and thus increased cost of electricity production. Drawing on William Kapp’s theory of social costs and ecological political economy, this article examines agrivoltaics developments within the latest EU-level policy initiatives on energy, agriculture, and climate change. Despite room for optimism regarding the comparative advantages of agrivoltaics, the findings reconcile these benefits with multiple trade-offs inherent in alleged ‘win–win’ solutions. Addressing the dual objectives of energy and agricultural transitions, the uncritical deployment of agrivoltaics risks perpetuating the prevailing ‘cheaper food paradigm’, characterised by capital and energy-intensive agricultural techniques, trade globalisation, wage compression, and the displacement and/or deferral of environmental harm. Additionally, rent-seeking behaviour among landowners leasing to energy developers could inflate agricultural land prices, thus exacerbating land ownership intensification and the financialisation of European farmland. This article concludes by advancing a few avenues to reinvest the rental income of agrivoltaics to facilitate the transition to agroecological farming practices.
Keywords: agricultural economics; biophysical economics; natural resource and energy economics; photovoltaics; political economy of energy; renewable energy